Long-term Outcomes after Second-Generation Cryoballoon Ablation of Atrial Fibrillation and Analysis of Risk Factors Related to Recurrence. Issue 3 (30th September 2022) - Dai, Yufan; Wang, Chenyuan; Wang, Zulu; Liang, Ming; Yang, Guitang; Jin, Zhiqing; Ding, Jian; Zhang, Ping; Han, Yaling
Abstract : Objective: This study is aimed to analyze the long-term safety and effectiveness of second-generation cryoballoon (CB2) ablation in the treatment of atrial fibrillation (AF). Methods: Data from 760 consecutive patients in the Department of Cardiology, General Hospital of Northern Theater Command from August 2016 to December 2018 with drug-refractory symptomatic AF undergoing pulmonary vein isolation (PVI) using CB2 were assessed. Procedure-related safety and freedom from AF and atrial flutter/atria tachycardia through 3 years were determined. The risk factors related to atrial tachyarrhythmia recurrence were analyzed. Results: Acute PVI was achieved in 100% of the 760 patients. Radiofrequency application for additional focal ablation was needed in 11 (1.4%) patients and for 14 pulmonary veins (0.5%, 14/(760 × 4)) to achieve PVI. A total of 748 patients, including 539 with paroxysmal AF (PAF) and 209 with persistent AF (SAF) completed the follow-up, and only 12 (1.6%) patients were lost. The mean follow-up duration was (19 ± 8) months. The rate of major complications was 0.9%, including 0.8% of right phrenic nerve injury, which resolved before discharge. Freedom from all tachyarrhythmias was achieved in 75.0%, 69.4%, and 63.2% of patients with PAF, respectively, at 12-, 24-, and 36-month follow-up, and in 75.1%, 67.4%, and 60.9% for SAF, with no significant differences between the PAF and SAF groups. AF course and the rate of body weight gain were independent risk factors for recurrence at 12 months after ablation ( P = 0.001 and P = 0.009, respectively). Conclusion: PVI using CB2 has a high acute success rate and good safety in the treatment of PAF and SAF. Long course of AF and weight gain after ablation were independent risk factors for recurrence.